INDICATORS OF TRAINEE TEACHER LEADERSHIP IN DISASTER MANAGEMENT FOR SCHOOLS IN MAHARASHTRA (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Disaster management in schools is a key component in ensuring the safety and well-being of the school, students and staff. Teacher trainees play a key role in enhancing disaster preparedness and resilience. This study focuses on identifying and analyzing key indicators of teacher trainee leadership in disaster management in the context of schools in Maharashtra. Teacher trainees from the College of Education need to have knowledge and awareness of student safety as well as local disasters while working as teachers in the future so that the severity of disasters in the context of the school can be reduced. Efforts should be made to emphasize on the decision-making skills, communication effectiveness and the ability to engage students and the school community in preparedness activities among student trainees. Training in disaster management is essential in teacher training programs. The need for disaster management is essential to equip teacher trainees as leaders in crisis situations.